Evaluation of Ir, Ru, and W as permanent modifiers for the simultaneous determination of As, Bi, Pb, Sb, and Se in natural water by electrothermal atomic absorption spectrometry - Freschi, GPG; Freschi, C. D.; Neto, JAG (Perkin-elmer Corp, 2006)
Iridium-, Ru-, and W-coated platforms were prepared by thermal treatment of the transversely heated graphite atomizer and investigated for the simultaneous determination of As, Bi, Pb, Sb, and Se in tap water by electrothermal atomic absorption spectrometry. The maximum pyrolysis temperature for As and Bi increased in a modifier sequence W < Ru < Ir. For Pb, Sb, and Se, this sequence was W < Ru, It. Calculated characteristic masses in the presence of It, Ru, and W were 35, 33, and 35 pg for As; 63, 51, and 52 pg for Bi; 50, 32, and 34 pg for Pb; 40, 35, and 31 pg for Sb; and 39, 39, and 93 pg for Se, respectively. Ruthenium was elected as the optimum modifier.Repeatability of the measurements was typically < 6%. Recoveries of As, Bi, Pb, Sb, and Se added to tap water samples varied from 79 to 109%. Accuracy was also checked by analysis of five certified reference materials (CRMs) from the National Institute of Standards and Technology (NIST1640 - Trace Elements in Natural Water; NIST 1643d Trace Elements in Water) and High Purity Standards (Trace Metals in Drinking Water Standards, lots #812708, #591107, and #710710). A paired t-test showed that the results for the CRMs were in agreement at the 95% confidence level with the certified values. The graphite tube lifetime was about 650 firings. multi-element determination is particularly challenging due to the necessity of carefully optimizing compromise conditions.Based on the considerations listed above, the aim of this paper was to evaluate the behavior of Ir, Ru, and W as permanent modifiers for the simultaneous determination of As, Bi, Pb, Sb, and Se. The performance of the proposed procedure was also verified after the ETAAS analysis of tap waters and reference materials.